PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, PROFITABILITAS, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Sonia Natalia; Anissa Amalia Mulya (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The purpose of this study is to investigate how tax avoidance is impacted by capital intensity, profitability, leverage, and corporate social responsibility. The dependent variable is tax avoidance, and the independent variables are capital intensity, profitability, leverage, and corporate social responsibility. With 95 businesses from the food and beverage manufacturing subsector listed on the Indonesia Stock Exchange between 2021 and 2024, this study makes use of secondary data. 44 businesses in all, spanning the observation years 2021–2024, were chosen as the research sample. Purposive sampling was the sample strategy used, while multiple linear regression was the analysis methodology. According to the study's findings, tax avoidance is significantly impacted by corporate social responsibility in both a partial and simultaneous manner. On the other hand, tax avoidance is not much impacted by leverage, profitability, or capital intensity..